Alternative Dispute Resolutions for Insurance disputes – Reconciliation and mediation as a model – - Afif, Mantaha Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the study to highlight the role of alternative means in the settlement of disputes in general and insurance disputes in particular and their effectiveness in ending the dispute and the statement of procedures used to resort to alternative means, and the researcher used the comparative analytical approach between Saudi Arabia in the adoption of reconciliation as a means An alternative alternative to dispute resolution and comparison with the Hashemite Kingdom of Jordan in the use of mediation as an alternative means of dispute resolution, by introducing alternative means of dispute resolution and its importance and with the statement of appropriate means to settle insurance disputes with the study of reconciliation procedures and mediation in the settlement of insurance disputes, the researcher reached the success of the outcomes of alternative means through settlement records or reconciliation records that express an executive basis ending the dispute after its approval by the competent authority, the researcher recommends The need to regulate alternative means of dispute resolution in Saudi Arabia within a regulated legal framework that deals with mediation, reconciliation and many friendly means of dispute resolution, in addition to spreading the culture of alternative means of dispute resolution to society and urging recourse to them.
Keywords: alternative means of dispute settlement; insurance disputes; conciliation; mediation; compulsory motor insurance